2018
DOI: 10.17241/smr.2018.00150
|View full text |Cite
|
Sign up to set email alerts
|

Are You Asking What Time Did Your Patients Go to Bed?: Getting the Short Sleep Onset Latency

Abstract: BRIEF COMMUNICATION A few patients diagnosed with insomnia attempt going to bed earlier to obtain adequate sleep and fall asleep less than 30 min, although they often complain about their inability to fall asleep easily. The aim of this study was to explore the association between short sleep latency and patients' sleepwake pattern. All the 99 patients with primary insomnia who were under treatment with benzodiazepine or non-benzodiazepine gamma-aminobutyric acid (GABA) agonists as sleeping pills were selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 17 publications
1
27
0
Order By: Relevance
“…Previously, we reported that a longer duration from wake-up time to bedtime predicts a short sleep latency (23). Since greater DBST may decrease the duration from wake-up to bedtime, it may also induce a longer sleep onset latency.…”
Section: Dbst: Predicting Insomnia Severitymentioning
confidence: 83%
See 2 more Smart Citations
“…Previously, we reported that a longer duration from wake-up time to bedtime predicts a short sleep latency (23). Since greater DBST may decrease the duration from wake-up to bedtime, it may also induce a longer sleep onset latency.…”
Section: Dbst: Predicting Insomnia Severitymentioning
confidence: 83%
“…It is a concept that is similar to the sleep restriction technique of the CBT-I. In a previous study, we reported that 17 hours of wakefulness is required for short sleep latency (23), and administering sleeping pills 7 hours before the waking-up time increases satisfaction with sleeping pills (17). The results showed that around 17 hours of wakefulness is needed for good sleep.…”
Section: Dbst: Predicted By Insomnia Severitymentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, going to bed early in the evening might increase the TIB during the night. Previously, we have reported that the duration from the wake-up time to bedtime in patients whose sleep latency was ≤30 min was longer than that of patients whose sleep latency was >30 min [ 7 ]. In addition, a longer duration from wake-up time to bedtime predicted a sleep latency ≤30 min in our previous study [ 28 ], which was conducted among cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…The desire of cancer patients to go to bed early in the evening may be related with their fatigue symptoms, which is common and can impair the circadian rhythm of these patients. 24 We can speculate that the late wake up time in the dissatisfied group may have been from fatigue. We did not measure the fatigue symptom in this study.…”
Section: Discussionmentioning
confidence: 93%